A fellow Swede is the reference for humanity. (27th January 2016) - Eriksson, Mats E.
Abstract : There is (or should be) an archived specimen, a reference copy if you like, for all living and fossil species that have been described scientifically. These physical specimens, so‐called name‐bearing type specimens, are housed at museums or academic institutes around the world for researchers to study and perhaps compare with their own material. But what about our own species, Homo sapiens ?